Gender, theatre, and the origins of criticism from Dryden to Manley : from Dryden to Manley - Frank, Marcie (Cambridge University Press, 2002)
Frank explores the theoretical and literary legacy of Dryden to a number of prominent women writers of the time. She proposes that Dryden develops a native literary tradition that is passed on as an inheritance to his heirs - Aphra Behn, Catharine Trotter, and Delarivier Manley.